AB0741 Can musculoskeletal ultrasonography examination (msus) predict outcome in shoulder impingement syndrome (sis)? a prospective blinded study. (23rd January 2014) - Khan, M.; McCreesh, K.; Saeed, A.; Ahern, T.; Fraser, A.
Abstract : Background: Steroid injection and active physiotherapy are the two standard conservative therapies used to treat SIS 1 and the outcome from these two treatments varies depending on numerous prognostic factors. Outcome predictors may identify patients suitable for specific therapies. The role of MSUS in the diagnosis of rotator cuff disease is well documented 2, however its utility in determining prognosis and selecting treatment pathways has not been yet assessed. Objectives: This prospective investigation was designed to assess the utility of MSUS in determining which patients may respond to guided steroid injection or active physiotherapy in SIS. Methods: Twenty consecutive patients with a new diagnosis of isolated SIS (symptoms duration less than 6 months) underwent MSUS. Participants chose to receive either ultrasound guided steroid injection or active physiotherapy. Participants were assessed at baseline, 6 weeks and 12 weeks. Assessments included shoulder pain and disability index (SPADI) and clinical assessment by an independent (blinded) rheumatologist. This clinical assessment included determination of the physician global assessment (PGA), the presence of Hawkins sign and the presence of supraspinatus tendon (SST) tenderness. Data are expressed as median (interquartile range) or as number (percentage). Results: At baseline and at 12 weeks there were no significant differences in assessed parameters. 12 (60%) of the cohort had an abnormal initial MSUS: of these 5 (42%) received a steroid injection and 7 (58%) received active physiotherapy. After six weeks those who received a steroid injection had significantly different clinical parameter measurements than those receiving active physiotherapy: – decrease in PGA was 80% (61-88%) vs 38% (30-43%, p=0.003); – decrease in SPADI was 85% (37-90%) vs 14% (10-23%, p=0.01); – resolution of SST tenderness occurred in 5 (100%) vs 0 (0%, p=0.003); and – resolution of Hawkins sign occurred in 4 (100%) vs 1 (14%, p=0.006). 10 (50%) of the cohort received a steroid injection: of these 5 (50%) received had an abnormal MSUS. After six weeks those with an abnormal MSUS had significantly different clinical parameters measurements than those with a normal MSUS: – decrease in PGA was 80% (61-88%) vs 20% (20-35%, p=0.008); – decrease in SPADI was 85% (37-90%) vs 19% (10-63%, p=0.05); – resolution of SST tenderness occurred in 5 (100%) vs 0 (0%, p=0.002); and – resolution of Hawkins sign occurred in 4 (100%) vs 0 (0%, p=0.002). Resolution of SST tenderness and Hawkins sign remained significantly different at 12 weeks. Conclusions: The presence of a significant structural abnormality at baseline MSUS suggests that outcome, in the short term at least, may be superior when patients receive a guided injection rather than physiotherapy. And conversely a normal baseline scan may indicate that physiotherapy is the preferred option. Adequately powered randomized clinical trials are required to determine whether treatment decision-making based on MSUS findings is superior to standard management without use of MSUS. References: Brox JI. Regional musculoskeletal conditions: shoulder pain. Best Pract Res Clin Rheumatol 2003; 17:33-56 Mack LA, Masten FA, Kilcoyne RF, Davies PK, Sickler ME. US evaluation of the rotator cuff. Radiology1985; 157:205 -209 Disclosure of Interest: None Declared